Upaya Meningkatkan Pelayanan Desain Grafis melalui Strategi Komunikasi Pemasaran Inovatif “Studi di Percetakan CV. Haikommikom” - Edward Fadly; Anang Anas Azhar (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The printing industry has undergone significant transformation due to digital technology and changes in consumer behavior. CV. Haikommikom, a printing company, faces challenges in improving the quality of graphic design services and expanding its market. This research aims to analyze the influence of innovative marketing communication strategies on the improvement of graphic design service quality at CV. Haikommikom and evaluate customer perceptions of these service changes. This study uses a qualitative method with a descriptive approach, collecting data through in-depth interviews and participatory observation. The results show that the implementation of marketing strategies through social media, personalized services with data analytics, and the use of advanced design technologies such as CorelDRAW and Photoshop significantly increase customer satisfaction and loyalty. Innovative marketing communication strategies have proven effective in improving the quality of graphic design services at CV. Haikommikom. The implementation of technology and personalized services not only increases customer satisfaction but also strengthens the company's position in the printing and graphic design industry. This finding underscores the importance of adapting technology and customer-focused marketing strategies to maintain competitiveness in the digital era.